The Ritual of Mbah-Mbeh Stone And Its Meaning for The Community of Watugaluh Village, Jombang - M. Kharis Majid; M. Nurrosyid Huda Setiawan; Amanda Puspa Rachima; Alysha Putri Siregar; Utdmah Mazirotus Sakinah (PURBAWIDYA, 2026)
This research focuses on the rituals related to the ancient stone “Mbah-Mbeh,” which is still preserved by the community of Watugaluh Village, Diwek District, Jombang Regency, East Java. The stone, believed to possess supranatural powers, serves as the center of various rituals to seek blessings, fertility, and protection. Using a phenomenological approach and qualitative descriptive methods, data were collected through participatory observation, in-depth interviews, and documentation. The findings showed that belief in the Mbah-Mbeh stone plays an important role in the spiritual and social life of the community. These rituals connected Islamic teachings, Javanese traditions, and local dynamism, while also serving as a form of ancestral reverence and a social bond that strengthens community cohesion and identity in the midst of modernization.